BIOSORPTION OF Cr(III) ION ON ALGAE Eucheuma spinosum BIOMASSA - I Wayan Sudiarta; Ni Putu Diantariani (Universitas Gadjah Mada, 2008)
Studies on biosorption and desorption of Cr(III) on algae (Eucheuma spinosum) adsorbent have been carried out. These studies included determination of biosorbent acidity, optimum pH, contact time of biosorption, isoterm and biosorption capacity, and mechanisms of interaction between Cr(III) and algae (E. spinosum) biosorben. Mechanisms of interaction were evaluated by sequential desorption of Cr(III) on algae biosorben by using aquadest, 1 M HCl and 0.05 M Na2EDTA. The result showed that the total acidity of algae biosorbent was 4.15 ± 0.33 mmol/g, the optimum pH was 3, and the optimum contact time was 20 min. Biosorption capacity of algae (E. spinosum) toward chromium (III) was 57.33 mg/g. The highest desorption of Cr(III) achieved when 1 M HCl was used, i.e. 51,01%, wheareas desorptions using aquadest and 0.05 M Na2EDTA were relatively low, i.e. 2.07% and 2.38% respectively. This result indicates that the main interaction mechanism of Cr(III) on algae was electrostatic attraction.